The Epic Pilgrimage: The Way of the Ascetics of El Capitan - Shultz, John (The international journal of religious tourism and pilgrimage, 2022)
El Capitan and its related environs constitute the ‘holiest of holies,’ the ‘center of the universe,’ or the ‘mecca’ of the rock climbing world. Big walls are simply the tallest, steepest, and most challenging rockfaces on the planet. For the tribe of big wall climbers, El Capitan, which stands nearly 1000 meters above the Merced River in Yosemite National Park in California, has a mystique and allure unmatched by any other location. In previous work, I establish the concept of climbing on El Capitan as ‘vertical pilgrimage’ (Shultz, 2020), and in this paper, I focus specifically on climbing efforts as pilgrimage asceticism. The research presented here is part of a larger effort focused on contemporary serial climbers on El Capitan, individuals who structure their entire lives around the cliff, and who return to the challenge again and again. The methods employed are generally ethnographic with elements of auto-ethnography. I consider whether two seminal theories of asceticism, Harpham (1992) and Valantasis (2008), survive out-of-sample testing with specific data from serial El Capitan climbers. To construct the analysis, I first, carefully consider the basic character of key movements of the pilgrimage from start to finish, including elements that are particularly austere in nature. Secondly, I consider, in detail, the language and interpretations of the El Capitan pilgrimage employed by four well-known ascensionists. Specific use of the term epic, which is ubiquitous in climbing discourse, is shown to hold significant meaning with respect to big wall asceticism. I conclude that these theories not only pass this out-of-sample test but can be shown to have significant descriptive utility with data related to these climbers. In particular, the ideas of Harpham and Valantasis potently describe how the culture of this famous rock arises from ascetic endeavors. Overall, this work demonstrates the tremendous potential of using an ascetical lens for analysis in the budding field of pilgrimage studies.